Early mental health exposure and clinical readiness of nursing students: A qualitative study - Bagus Dwi Cahyono; Ronal Surya Aditya; Nurul Huda; Apriana Rahmawati; Evy Aristawati (KHD-Production, 2026)
Early experiential exposure is increasingly advocated to enhance psychiatric clinical readiness; however, empirical evidence regarding real-world social rehabilitation settings remains limited, particularly within low- and middle-income countries where clinical placements are often delayed. This study examined nursing students’ learning experiences and perceived clinical readiness following early exposure to individuals with mental disorders in a community rehabilitation setting. A qualitative descriptive design utilizing reflexive thematic analysis was conducted with 35 third-semester Diploma nursing students in East Java, Indonesia. Purposive sampling achieved thematic saturation at 28 interviews. Data were collected via semi-structured interviews and analyzed using reflexive thematic analysis, adhering strictly to COREQ reporting standards to ensure methodological transparency. Findings delineated a developmental trajectory from initial stigma and anxiety toward empathy, therapeutic confidence, and clinical preparedness. Four interconnected themes emerged: (1) attitudinal reconstruction regarding mental illness, (2) emerging relational agency in therapeutic communication, (3) cognitive-affective integration of theoretical constructs, and (4) transitional clinical readiness. Supervised face-to-face engagement within a supportive rehabilitation environment, facilitated stigma deconstruction, and cultivated adaptive interpersonal competencies. It contextualized abstract classroom knowledge through authentic patient interaction, thereby bridging the theory-practice divide. Early structured exposure transcends passive observation, functioning as a transformative pedagogical mechanism that synchronizes affective, cognitive, and relational development. Systematically embedding community-based experiential learning prior to acute psychiatric placements is critical to optimizing global clinical readiness, mitigating entrenched stigma, and advancing recovery-oriented nursing curricula worldwide, particularly in resource-constrained educational systems